Method for the determination of tetrachloromethane, trichloroethane, 1,1,2-trichloroethane, and tetrachloroethene in the air at workplaces - Joanna Kowalska; Małgorzata Szewczyńska (Nofer Institute of Occupational Medicine, 2023)
Background Chemical substances from the halogenated aliphatic hydrocarbons group are used in industry, e.g., as intermediates in syntheses, auxiliaries, solvents in degreasing processes, and laboratory tests. Due to their harmful effects on human health and the environment, their use is often banned or limited to certain industrial uses only. Material and Methods A sorbent tube containing 2 layers (100/50 mg) of coconut shell charcoal was used as a sampler for air sampling. Gas chromatography-mass spectrometry technique and the use of HP-5MS column (30 m × 0.25 mm × 0.25 μm), an oven temperature ramp program from 40°C to 250°C and selected ion monitoring mode were chosen for the determination. Results The established chromatographic conditions enable the simultaneous determination of tetrachloromethane, trichlorethane, 1,1,2-trichloroethane and tetrachloroethene in the concentration range 2-100 μg/ml. The average desorption coefficients obtained were: 0.97 for tetrachloromethane, 0.96 for trichloroethene, 0.96 for 1,1,2-trichloroethane and 0.96 for tetrachloroethene. Conclusions The calculation of the substance concentration in the analyzed air requires the determination of the amount of substances trapped by the sorbent tube, the desorption coefficient and the air sample volume. Adequate dilution of the extract makes it possible to determine tetrachloromethane, trichloroethene, 1,1,2-trichloroethane and tetrachloroethene in ranges corresponding to 0.1-2 times the maximum admissible concentrations in the workplace air. This article discusses the issues occupational safety and health, which are the subject matter of health sciences and environmental engineering research. Med Pr. 2023;74(1):53-62